Exploring Differentiated Instruction Strategies in Arabic Teaching for Heterogeneous Classrooms: A Constructivist Learning Framework / استكشاف استراتيجيات التعليم المتمايز في تدريس اللغة العربية للفصول الدراسية المتغايرة: إطار تعلم بنائي - Ibnu Fitrianto; Sharif El-Amina; William Davidson (IJAS: International Journal of Arabic Studies, 2026)
This study explores the implementation of differentiated instruction strategies in Arabic language teaching within heterogeneous classrooms using a constructivist learning framework. The research investigates how instructional differentiation can effectively accommodate diverse learner needs, linguistic backgrounds, and learning styles while fostering meaningful engagement and improved language outcomes. Employing a qualitative methodology, the study analyzes classroom practices, teacher strategies, and learner responses to identify key patterns that support successful differentiation. Findings reveal that constructivist-based differentiation—such as scaffolding, flexible grouping, tiered tasks, and formative assessment—significantly enhances students’ participation, motivation, and comprehension. The results also show that differentiated instruction strengthens autonomy and encourages collaborative knowledge construction, aligning with the principles of student-centered learning. Despite its benefits, challenges such as limited teacher training, large class sizes, and time constraints hinder optimal implementation. The study concludes that sustained professional development and institutional support are essential for advancing differentiated instruction in Arabic language education. These findings contribute to the growing body of research advocating pedagogical approaches that value learner diversity and promote equitable learning opportunities.